2010
DOI: 10.1098/rstb.2009.0289
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic discrimination of sympatric morphs in Darwin's finches: a behavioural mechanism for assortative mating?

Abstract: Populations with multiple morphological or behavioural types provide unique opportunities for studying the causes and consequences of evolutionary diversification. A population of the medium ground finch (Geospiza fortis) at El Garrapatero on Santa Cruz Island, Galápagos, features two beak size morphs. These morphs produce acoustically distinctive songs, are subject to disruptive selection and mate assortatively by morph. The main goal of the present study was to assess whether finches from this population are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
50
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 52 publications
(91 reference statements)
5
50
0
Order By: Relevance
“…Experiments in the field have demonstrated that closely related species in the genus Geospiza living sympatrically can discriminate between each other on the basis of song in the absence of visual cues (5,6) and on the basis of morphology in the absence of acoustic cues or movement (7). Furthermore, discrimination between allopatric populations of the same species is possible when they differ in song (5,8,9) or morphology (7).…”
mentioning
confidence: 99%
“…Experiments in the field have demonstrated that closely related species in the genus Geospiza living sympatrically can discriminate between each other on the basis of song in the absence of visual cues (5,6) and on the basis of morphology in the absence of acoustic cues or movement (7). Furthermore, discrimination between allopatric populations of the same species is possible when they differ in song (5,8,9) or morphology (7).…”
mentioning
confidence: 99%
“…We here used the same playback stimuli from the geographic song discrimination component of Podos (2010). In brief, we identified high-quality versions of songs recorded during our 2004 and 2005 visits to Borrero Bay (see above for recording methods).…”
Section: Playback Stimulimentioning
confidence: 99%
“…We assumed that all of our Borrero Bay singers were smallmorphed, based on annotations taken during recording and also given that large-morphed birds at Borrero Bay are rare (Hendry et al, 2006). Following Podos (2010), and as with our analysis of geographical variation in song structure (see above), we accounted for the presumed small-morph bias in our Borrero Bay playback stimuli by restricting our selection of playback songs from El Garrapatero to small-morphed singers from that site. For each of 18 playback stimuli (2 sequences for each of the 9 subjects), we prepared a playback sequence consisting of 18 repetitions of each song, played every 10 s for 3 min.…”
Section: Playback Stimulimentioning
confidence: 99%
See 2 more Smart Citations